The Influence of the PnP and NHT Cooperative Learning Models on Natural and Social Sciences (IPAS) Student Learning Outcomes in Elementary Schools - Maling, Penny (Universitas Pendidikan Indonesia Kampus Serang, 2024)
The students' low learning outcomes suggest they struggle to grasp the material, likely due to boredom and passivity in class. To address this, teachers need innovative learning models that engage students actively. This study aimed to assess the impact of Picture and Picture (PnP) and Numbered Head Together (NHT) Cooperative Learning Models on fourth-grade students' learning outcomes in Natural Sciences and Social Sciences. Using a quasi-experimental method in two classes, the researcher found that in the first class, the average difference between using PnP and NHT was 17.62 points, while in the second class, the average difference was 21.19 points. Both classes show that PnP values are higher than NHT. The results of the t-test analysis show that in the two schools, there is a significant difference between the average score of PnP and NHT group (sig. values 0.005 and 0.006), so it is assumed that PnP is more effective than NHT. The research indicates that employing picture-based learning can significantly enhance learning outcomes compared to methods lacking visual aids. In conclusion, there is a difference in students' learning outcomes in the Sciences and Social Sciences (IPAS) subjects for fourth-graders of the State Elementary School of Kutowinangun 07 and State Elementary School of Kutowinangun 01 using PnP and NHT. The lack of direct media in the NHT class hindered understanding and effectiveness. In contrast, the PnP class's use of visually stimulating picture media enhanced engagement and learning outcomes. Students were more focused and participative, leading to significant improvements compared to other similar learning models.